2015
DOI: 10.1128/jvi.02077-14
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory Effects of Interferon Gamma in Mouse Adenovirus 1 Myocarditis

Abstract: Adenoviruses are frequent causes of pediatric myocarditis. Little is known about the pathogenesis of adenovirus myocarditis, and the species specificity of human adenoviruses has limited the development of animal models, which is a significant barrier to strategies for prevention or treatment. We have developed a mouse model of myocarditis following mouse adenovirus 1 (MAV-1) infection to study the pathogenic mechanisms of this important cause of pediatric myocarditis. Following intranasal infection of neonata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 61 publications
(78 reference statements)
4
45
1
Order By: Relevance
“…It is possible that these differences could occur in an organ-specific manner. Consistent with that possibility, we have demonstrated that MAV-1-induced IFN-γ production is lower in the lungs of neonatal mice compared to adults (Procario et al, 2012), while IFN-γ production is substantially greater in hearts of infected neonates than in adults (McCarthy et al, 2015). …”
Section: Discussionsupporting
confidence: 80%
“…It is possible that these differences could occur in an organ-specific manner. Consistent with that possibility, we have demonstrated that MAV-1-induced IFN-γ production is lower in the lungs of neonatal mice compared to adults (Procario et al, 2012), while IFN-γ production is substantially greater in hearts of infected neonates than in adults (McCarthy et al, 2015). …”
Section: Discussionsupporting
confidence: 80%
“…Although IFN-γ does not exert a critical antiviral function during MAV-1 respiratory infection (Anderson et al, 2009; McCarthy et al, 2015b) or myocarditis (McCarthy et al, 2015a), we demonstrated that it is necessary for virus-induced inflammatory responses in the hearts of MAV-1-infected mice (McCarthy et al, 2015a). In the present study, we tested the hypothesis that IFN-γ-induced immunoproteasome activity is an important contributor to virus-induced inflammation.…”
Section: Introductionmentioning
confidence: 84%
“…We have used mouse adenovirus type 1 (MAV-1) to study the pathogenesis of adenovirus respiratory infection in its natural host (McCarthy et al, 2013; McCarthy et al, 2015b; McCarthy et al, 2014; Procario et al, 2012; Procario et al, 2016; Weinberg et al, 2005). Recently, we used MAV-1 to establish a mouse model of adenovirus myocarditis (McCarthy et al, 2015a) in which intranasal (i.n.) MAV-1 infection of neonatal C57BL/6 (B6) mice induces interferon gamma (IFN-γ) expression in the heart along with cellular inflammation, cardiac myocyte necrosis, and decreased cardiac contractility.…”
Section: Introductionmentioning
confidence: 99%
“…10). IFN-␥ is commonly produced by effector CD8 ϩ T lymphocytes, and upon recognition of the specific antigen, CTL activity can be measured (38,39). Several studies conducted in mice have demonstrated an important role for IFN-␥ in immune protection from herpesvirus infections (40,41).…”
Section: Figmentioning
confidence: 99%